Responses of Australian sea lions, Neophoca cinerea, to anthropogenic activities in the Perth metropolitan area, Western Australia - Osterrieder, S.; Salgado Kent, Chandra; Robinson, R. (2016)
Tourist-based activities, partly due to their rapid increase, have raised concerns regarding the impacts of anthropogenic activity on marine fauna. Documented effects on pinnipeds in proximity to humans include changes in behaviour, site use and potentially higher aggression levels towards people. Effects vary considerably between populations and sites, thus requiring separate assessment of human impacts on activity and energy budgets. Responses of the endangered Australian sea lion, Neophoca cinerea, to human visitation were recorded from November 2013 through April 2014. Exposure levels and response types to anthropogenic activities were assessed at two easily accessible locations with different management schemes, Seal (landing prohibited) and Carnac (landing permitted) islands, Western Australia. Exposure levels were measured as both stimulus type (i.e. 'People', 'Paddlers', 'Small', 'Medium', and 'Large vessels', 'Tour vessels', and 'Jet skies'), and people ('Direct', 'Attract', 'Interact', 'View', 'Incidental', 'Water', 'Low-level'), and vessel activities ('Interact', 'Approach/Follow', 'Anchor noise', 'Engine noise', 'Close to beach', 'Moderate/Fast travel', 'Slow travel', 'Transit', 'Drift/At anchor', 'Aircraft noise'). Exposure levels varied significantly between the islands in numbers, stimuli type, duration and minimum approach distances. The instantaneous behaviours of 'Lift head', 'Interact' and 'Sit' were the most frequent responses. 'Aggressive' and 'Retreat' responses, the highest disturbance levels measured, occurred on Carnac approximately once per day, but rarely on Seal Island. 'Aggressive' behaviour towards 'People' was observed only on Carnac Island and elicited only by 'People'. 'People', 'Tour vessels', and scenic 'Aircrafts' on both islands as well as 'Jet skis' on Carnac Island had the highest probability of triggering responses. Owing to their relatively high visitation at Seal Island, 'Paddle powered vessels', followed by 'Tour vessels' elicited the highest number of responses, compared with 'People', 'Small', and 'Medium vessels' at Carnac Island. The majority of responses occurred when any stimulus type was at short-range (=10 m), and 'People' 'Viewing' N. cinerea elicited most. Vessels triggered more responses at larger ranges than 'People'. To limit close-range access to N. cinerea, one possibility is to close the beach at Carnac Island to human visitation and increase the minimum approach distance by vessels and 'People' by installing marker buoys at least 15 m from the shore.